A Cross-Reactive Humanized Monoclonal Antibody Targeting Fusion Glycoprotein Function Protects Ferrets Against Lethal Nipah Virus and Hendra Virus Infection. (4th November 2019) - Mire, Chad E; Chan, Yee-Peng; Borisevich, Viktoriya; Cross, Robert W; Yan, Lianying; Agans, Krystle N; Dang, Ha V; Veesler, David; Fenton, Karla A; Geisbert, Thomas W; Broder, Christopher C
Abstract: Background: Nipah virus (NiV) and Hendra virus (HeV) are zoonotic paramyxoviruses that cause severe disease in both animals and humans. There are no approved vaccines or treatments for use in humans; however, therapeutic treatment of both NiV and HeV infection in ferrets and non-human primates with a cross-reactive, neutralizing human monoclonal antibody (mAb), m102.4, targeting the G glycoprotein has been demonstrated. In a previous study, we isolated, characterized, and humanized a cross-reactive, neutralizing anti-F mAb (h5B3.1). The mAb h5B3.1 blocks the required F conformational change needed to facilitate membrane fusion and virus infection, and the epitope recognized by h5B3.1 has been structurally defined; however, the efficacy of h5B3.1 in vivo is unknown. Methods: The post-infection antiviral activity of h5B3.1 was evaluated in vivo by administration in ferrets after NiV and HeV virus challenge. Results: All subjects that received h5B3.1 from 1 to several days after infection with a high-dose, oral-nasal virus challenge were protected from disease, whereas all controls died. Conclusions: This is the first successful post-exposure antibody therapy for NiV and HeV using a humanized cross-reactive mAb targeting the F glycoprotein, and the findings suggest that a combination therapy targeting both F and G should be evaluated as a therapy for NiV/HeV infection.